Decolourisation studies of azo dyes by locally isolated fungi for application as bioremediation agent - Voon, C.Y (Universiti Malaysia Sarawak, UNIMAS, 2013)
The four fungal isolates namely Marasmius cladophyllus, Cerrena unicolor, Cunninghamella bainieri and Trichoderma harzianium were used in the study of dye decolourisation. Orange G was chosen as a representative of azo dyes in the decolourisation study. The fungal isolates were used in Orange G decolourisation study in both solid and liquid culture conditions. The study was carried out to test for the ability of locally isolated fungi in dye degradation. It is also hoped that the ligninolytic enzymes can be identified and characterized at the end of experiment. The results showed that M. cladophyllus MS8 could decolourise Orange G completely in solid GMM agar on day 7. Spectrophotometer analysis revealed that M. cladophyllus MS8 could remove 56.33% of Orange G in liquid GMM on the 16th day of decolourisation experiments. The enzyme assays conducted showed that laccase, manganese peroxidase and lignin peroxidase were responsible for the Orange G decolourisation. Maximum percentage of Orange G decolourisation was recorded under optimal experimental condition with the present of dye at a final concentration of 0.02% (w/v) and by two fungal plugs as inoculums. The Orange G was decolourised rapidly initially in the 3 days pre-grown culture but only 40.90% of percentage of decolourisation was achieved. RBBR was decolourised by M. cladophyllus MS8 effectively with 98.56% of color removal on the 8 th day. These therefore show the interesting potential of fungal isolate M. cladophyllus MS8 for dye decolourisation.